Pengaruh Kontrol Diri terhadap Tingkat Kecanduan Game online di Kalangan Mahasiswa - Arriana Puspita Sari; Cindy Claudia; Lailatul Fathya; Diva Ayunda Tobing; Dini Syah Fitri; Gebby Geraldina; Dita Novita (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
In today’s digital era, the rapid advancement of technology has reshaped the way people seek entertainment, with online games becoming a dominant pastime, particularly among university students. While gaming provides an outlet for relaxation and escapism, its excessive use often leads to addictive behaviors that interfere with academic responsibilities, physical health, and social functioning. This research was designed to explore how self-control influences the tendency toward online game addiction among students. Utilizing a quantitative correlational method, the study gathered data from 111 university students across various disciplines who actively engage in online gaming. The measurement tools consisted of validated Likert-scale questionnaires, and statistical analysis was conducted using simple linear regression. The findings revealed a statistically significant negative relationship between self-control and gaming addiction, indicating that individuals with stronger self-regulation skills are less likely to develop problematic gaming behaviors. These results highlight the vital role of self-control in maintaining a balanced academic and personal life. The study emphasizes the need for strategic interventions within educational settings to foster better emotional regulation among students as a preventative measure against gaming addiction.